138 The role of hospital representatives in increasing engagement in student feedback. (16th November 2020) - Malik, Amman; Mostafa, Omar; Shah, Haroon
Abstract : Student representatives, termed 'Academic Representatives' (AR), at the University of Birmingham act as intermediaries for their respective year group by relaying feedback to, and working with, medical school staff (MSS) to resolve any academic issues that arise, as well as wellbeing concerns. Owing to large cohort sizes (405 students in Year 3 2019/20), various feedback methods have historically been employed to effectively gather cohort feedback to ensure student concerns can be relayed in a method which is accessible to all, but also manageable for the sole year group AR. As students enter different hospital placements in their third year, the task of gathering feedback becomes more challenging. A novel method was devised where Hospital Representatives (HR) would be assigned to each hospital to assist the Year 3 AR in gathering and assimilating feedback to present to MSS responsible for Year 3 medical students. Thus, we aimed to assess whether HRs are indeed a feasible and effective method in gathering feedback in the clinical years. We based our analysis on qualitative responses as reported by medical students, HRs, AR and MSS. As reported by students, the personal interaction with HRs was more encouraging and welcoming compared to previous methods, increasing the yield in feedback garnered. Meanwhile, MSS reported the feedback to be more in-depth and practical. They were able to focus on individual hospitals and tailor resources where needed, owing to different clinical experiences students experienced across different hospital trusts. The AR reported the benefits of not having to physically travel to each hospital; more time could be spent addressing individual issues raised, or on their own medical studies. To conclude, deploying HRs across different placements has proved to be efficacious, fruitful and resourceful. Thus, we recommend this strategy be implemented on a larger scale at other medical schools and institutions.